1998
DOI: 10.1073/pnas.95.6.3106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soybean phytoestrogen intake on low density lipoprotein oxidation resistance

Abstract: The oxidation of low density lipoproteins (LDLs) is thought to take place in the arterial intima when the particles have become isolated from circulating water-soluble antioxidants. We hypothesized that isof lavonoid antioxidants derived from soy could be incorporated into lipoproteins and possibly could protect them against oxidation, which is regarded as atherogenic. Six healthy volunteers received 3 soy bars [containing the isof lavonoid antioxidants genistein (12 mg) and daidzein (7 mg)] daily for 2 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
162
3
8

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 356 publications
(189 citation statements)
references
References 24 publications
10
162
3
8
Order By: Relevance
“…The concentrations of DAI in the different fractions obtained after lipoprotein separation of 2 ml plasma were measured by GC/MS using a stable isotopically labelled internal standard [3,4,[8][9][10][11][12][13] C]DAI. Total DAI was determined after extraction and enzymic hydrolysis with a mix of b-glucuronidase and sulfatase.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The concentrations of DAI in the different fractions obtained after lipoprotein separation of 2 ml plasma were measured by GC/MS using a stable isotopically labelled internal standard [3,4,[8][9][10][11][12][13] C]DAI. Total DAI was determined after extraction and enzymic hydrolysis with a mix of b-glucuronidase and sulfatase.…”
Section: Methodsmentioning
confidence: 99%
“…The separated lipoprotein fractions were equilibrated with 100 pmol [3,4,[8][9][10][11][12][13] C]DAI for 30 min at room temperature and diluted with five volumes of 0·5 M-triethylammonium sulfate (pH 5). Further details on sample clean-up, enzymic hydrolysis and derivatisation for GC/MS analysis are described by Rüfer et al (4) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is limited evidence in humans that bone metabolism is affected favorably by the isoflavone derivative ipriflavone [21] and by soy isoflavones [22,23]. Studies in humans have shown that phytoestrogens decrease plasma lipids [24,25], LDL oxidation [26,27], arterial compliance [28] and endothelial cell damage [26]. These observations are strengthened by experimental data in atherosclerotic non-human primates, indicating that cardiovascular risk factors [29,30], coronary artery atherosclerosis [31], coronary vascular reactivity [32] and aortic cholesteryl ester content [30] are influenced favorably.…”
Section: Introductionmentioning
confidence: 99%